Acute thrombocytopenia: picking a way through a paucity of platelets. (2nd September 2019) - Musson, E Nuttall; Lomas, O; Murphy, MF
Abstract : Thrombocytopenia is defined as a platelet count under 150x10 9 /litre. It may be found as a bystander to other pathology or directly related to an underlying haematological condition. Apart from laboratory artefact, it should be treated seriously as it often reflects serious underlying disease. This review uses short case histories to illustrate how to approach thrombocytopenia during the initial presentation of an adult patient to hospital. This article guides the general hospital physician through the narrow but potentially confusing differential diagnoses related to thrombocytopenia, with particular focus on immune thrombocytopenia, disseminated intravascular coagulation and thrombotic thrombocytopenic purpura. Thrombocytopenia in pregnancy deserves special consideration and will not be discussed in this article.